RUNX3 gene promoter demethylation by 5-Aza-CdR induces apoptosis in breast cancer MCF-7 cell line - Kang, Hua-Feng (Dove Medical Press, 2013)
Runt-related transcription factor 3 (RUNX3) is a tumor suppressor gene, its inactivation due to hypermethylation related to carcinogenesis. The aim of this study was to investigate the effects of 5-aza-2′-deoxycytidine (5-Aza-CdR) on cell proliferation and apoptosis by demethylation of the promoter region and restoring the expression of RUNX3 in the breast cancer MCF-7 cell line. MCF-7 cells were cultured with different concentrations (0.4–102.4 μmol/L) of 5-Aza-CdR in vitro. MTT assay was used to determine the proliferation of MCF-7 cells. Flow cytometry and Hoechst staining were used for analyzing cell apoptosis. The methylation status and expression of RUNX3 in mRNA and protein levels were measured by methylation-specific polymerase chain reaction (PCR [MSP]), reverse transcription (RT)-PCR, and Western blot. It was shown that the RUNX3 gene downregulated and hypermethylated in MCF-7 cells. 5-Aza-CdR induced demethylation, upregulated the expression of RUNX3 on both mRNA and protein levels in cancer cells, and induced growth suppression and apoptosis in vitro in a dose- and time-dependent manner. The results demonstrate that RUNX3 downregulation in breast cancer is frequently due to hypermethylation, and that 5-Aza-CdR can inhibit cell proliferation and induce apoptosis by eliminating the methylation status of RUNX3 promoter and restoring its expression.